Partnership Quality, Student's Satisfaction, and Loyalty: A Study at Higher Education Legal Entities in Indonesia - Supriyanto Achmad; Sumarsono Raden Bambang; Sunandar Asep; Rochmawati; Dami Zummy Anselmus; Ratri Dwi Kurnianing; Ardian Nur Luthfi (De Gruyter, 2024)
Partnership among higher education institutions serves as the central element for sustainable development. The quality of their partnerships is highly necessary for higher education development, specifically in academic infrastructure, curriculum design, pedagogical practices, and financial frameworks. This progression is expected to enhance students' satisfaction and loyalty. Therefore, this study explores the effects of partnerships among higher education institutions with legal entities on students' satisfaction and loyalty. Accordingly, this research adopted a quantitative descriptive and regressive survey approach. The research population consisted of students from a university with a legal entity. At the same time, the sample was taken through purposive sampling with the criteria of having interacted or received services from the university's partner with a legal entity. Data were garnered through questionnaires, which have been declared valid and reliable. The collected data were analyzed using the structural equation model technique through Structural Equation Modeling-Partial Least Squares with SmartPLS 3 application. The research results indicate the following: (1) partnership quality (PQ) directly influences student satisfaction (SS), (2) SS directly affects student loyalty (SL), (3) PQ of higher education institutions with legal entity presents no effects on SL, and (4) PQ indirectly affects SL through SS.